2009
DOI: 10.1111/j.1758-2229.2009.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Substantial high‐affinity methanotroph populations in Andisols effect high rates of atmospheric methane oxidation

Abstract: Methanotrophic bacteria in soils derived from volcanic ash (Andisols) were characterized via time series (13) C-phospholipid fatty acid (PLFA) labelling. Three Andisols were incubated under 2 ppmv (13) CH4 for up to 18 weeks, thus enabling high-affinity methanotrophs to be selectively characterized and quantified. PLFA profiles from all soils were broadly similar, but the magnitude of the high-affinity methanotrophic populations determined through (13) C-PLFA-stable isotope probing displayed sizeable differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In some of the cave population datasets (e.g., from Portugal), the USCα sequences even exhibited a considerably higher relative abundance of up to 10% of the total microbial community, indicating not only the presence but also potential key role of USCα in these environments. There have been very few indications for the presence of atmospheric methane oxidation, for example, in volcanic soil environments on Hawaii and andisols on Tenerife (King and Nanba, ; Maxfield et al ., ), and it was so far postulated that the atmospheric methanotrophs are dependent on vegetated ecosystems with significant soil accumulation (King and Nanba, ) (hence the name ‘upland soil’ cluster). The unexpected presence of USCα 16S rRNA gene sequences in datasets from cave wall biofilms and subterranean ecosystems around the world (Hawaii‐USA, Azores/Portugal, Tenerife/Spain, USA, Venezuela, Mexico, China, Iceland, Korea, Slovenia, Bosnia and Herzegovina) show that this might not be accurate, further supported by the presence of biofilm‐related capacities in the USCα draft genome.…”
Section: Resultsmentioning
confidence: 99%
“…In some of the cave population datasets (e.g., from Portugal), the USCα sequences even exhibited a considerably higher relative abundance of up to 10% of the total microbial community, indicating not only the presence but also potential key role of USCα in these environments. There have been very few indications for the presence of atmospheric methane oxidation, for example, in volcanic soil environments on Hawaii and andisols on Tenerife (King and Nanba, ; Maxfield et al ., ), and it was so far postulated that the atmospheric methanotrophs are dependent on vegetated ecosystems with significant soil accumulation (King and Nanba, ) (hence the name ‘upland soil’ cluster). The unexpected presence of USCα 16S rRNA gene sequences in datasets from cave wall biofilms and subterranean ecosystems around the world (Hawaii‐USA, Azores/Portugal, Tenerife/Spain, USA, Venezuela, Mexico, China, Iceland, Korea, Slovenia, Bosnia and Herzegovina) show that this might not be accurate, further supported by the presence of biofilm‐related capacities in the USCα draft genome.…”
Section: Resultsmentioning
confidence: 99%
“…h −1 (Maxfield et al 2009). What are the spatial factors controlling this variable methane oxidation rates?…”
Section: Summary and Future Perspectivesmentioning
confidence: 96%
“…Molecular‐based studies clearly show the presence of a number of pmoA genes representing these high‐affinity methanotrophs in forest and upland soils and recently important work by Liesack and colleagues (Baani and Liesack, 2008) demonstrated that Methylocystis strain SC2 has an alternative pMMO system that oxidizes methane at very low concentrations, hinting at the likely identity of this high‐affinity group. In this volume, Maxfield and colleagues (2009) describe the use of 13 CH 4 labelling of PLFAs of high‐affinity methanotrophs in soils derived from volcanic ash (Andisols) and show that these soils, which have not been examined before, are very active in oxidizing atmospheric concentrations of methane. A mini‐review by Kolb (2009) draws together all of the current information on the quest for atmospheric methane oxidizers in forest soils and suggests future directions that research needs to take in order to fully understand this very important process.…”
Section: Diversity Of Metabolismmentioning
confidence: 99%